2003
DOI: 10.1524/zpch.217.5.479.20457
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Halide Ions on the Kinetics of Electrochemical Copper(II) Reduction

Abstract: Electrochemistry / Copper / Halides / Mechanism / Electroplating / ElectrorefiningThe cathodic reduction of copper(II) in an electrolyte comparable to technical conditions (2.2 M H 2 SO 4 + 0.3 M CuSO 4 ) is markedly affected by the presence of small concentrations of halide ions. Chloride ions accelerate the reaction, while it is slowed down by bromide. Experiments in which cyclic voltammetry is combined with an electrochemical quartz-crystal microbalance reveal the deposition and dissolution of crystalline C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 24 publications
5
46
0
Order By: Relevance
“…The value of j 0 obtained in this study is somewhat larger than the previously reported values (1.1-1.4 mA cm −2 ), which is most likely due to the difference in the concentrations of Cu 2+ ions in this study (0.85 M) and those in the previous study (0.25 M). The Tafel slope was 124 mV/decade, which is also similar to the literature values [27][28][29]. Substituting the obtained kinetic parameter values of α and j 0 into the Overpotential / V Fig.…”
Section: Methodssupporting
confidence: 86%
“…The value of j 0 obtained in this study is somewhat larger than the previously reported values (1.1-1.4 mA cm −2 ), which is most likely due to the difference in the concentrations of Cu 2+ ions in this study (0.85 M) and those in the previous study (0.25 M). The Tafel slope was 124 mV/decade, which is also similar to the literature values [27][28][29]. Substituting the obtained kinetic parameter values of α and j 0 into the Overpotential / V Fig.…”
Section: Methodssupporting
confidence: 86%
“…Similarly, the possibility of CuCl precipitation should also be considered. 37,38 In any case, the sharp onset of current is suggestive of a classical heterogeneous nucleation triggered process.…”
Section: Resultsmentioning
confidence: 94%
“…It can be assumed that CuX bulk phases (X = Br ) , Cl ) ) would also appear upon copper dissolution provided higher chloride and bromide concentrations are used. E.g., Dobelhofer et al report the formation of crystalline CuCl bulk and CuBr bulk upon copper deposition from acidic electrolytes containing 0.3 M CuSO 4 , 2.2 M H 2 SO 4 and trace amounts of halides (2 mM Br ) or Cl ) , respectively) [35]. Here, it is the high concentration of cuprous ions which gives rise to the exceeding of the CuX bulk solubility product upon copper deposition.…”
Section: Discussionmentioning
confidence: 99%